Phthalocyanine-Conjugated Upconversion NaYF4 :Yb3+ /Er3+ @SiO2 Nanospheres for NIR-Triggered Photodynamic Therapy in a Tumor Mouse Model - Kostiv, Uliana; Patsula, Vitalii; Noculak, Agnieszka; Podhorodecki, Artur; Větvička, David; Poučková, Pavla; Sedláková, Zdenka; Horák, Daniel (ChemMedChem, 2017)
Photodynamic therapy (PDT) has garnered immense attention as a minimally invasive clinical treatment modality for malignant cancers. However, its low penetration depth and photodamage of living tissues by UV and visible light, which activate a photosensitizer, limit the application of PDT. In this study, monodisperse NaYF4 :Yb3+ /Er3+ nanospheres 20 nm in diameter, that serve as near-infrared (NIR)-to-visible light converters and activators of a photosensitizer, were synthesized by high-temperature co-precipitation of lanthanide chlorides in a high-boiling organic solvent (octadec-1-ene). The nanoparticles were coated with a thin shell (≈3 nm) of homogenous silica via the hydrolysis and condensation of tetramethyl orthosilicate. The NaYF4 :Yb3+ /Er3+ @SiO2 particles were further functionalized by methacrylate-terminated groups via 3-(trimethoxysilyl)propyl methacrylate. To introduce a large number of reactive amino groups on the particle surface, methacrylate-terminated NaYF4 :Yb3+ /Er3+ @SiO2 nanospheres were modified with a branched polyethyleneimine (PEI) via Michael addition. Aluminum carboxyphthalocyanine (Al Pc-COOH) was then conjugated to NaYF4 :Yb3+ /Er3+ @SiO2 -PEI nanospheres via carbodiimide chemistry. The resulting NaYF4 :Yb3+ /Er3+ @SiO2 -PEI-Pc particles were finally modified with succinimidyl ester of poly(ethylene glycol) (PEG) in order to alleviate their future uptake by the reticuloendothelial system. Upon 980 nm irradiation, the intensive red emission of NaYF4 :Yb3+ /Er3+ @SiO2 -PEI-Pc-PEG nanoparticles completely vanished, indicating efficient energy transfer from the nanoparticles to Al Pc-COOH, which generates singlet oxygen (1 O2 ). Last but not least, NaYF4 :Yb3+ /Er3+ @SiO2 -PEI-Pc-PEG nanospheres were intratumorally administered into mammary carcinoma MDA-MB-231 growing subcutaneously in athymic nude mice. Extensive necrosis developed at the tumor site of all mice 24-48 h after irradiation by laser at 980 nm wavelength. The results demonstrate that the NaYF4 :Yb3+ /Er3+ @SiO2 -PEI-Pc-PEG nanospheres have great potential as a novel NIR-triggered PDT nanoplatform for deep-tissue cancer therapy.
Keywords: Animals; Indoles; proliferace buněk; Fluorides; vztah mezi dávkou a účinkem léčiva; Silicon Dioxide; Female; indoly; Cell Line, Tumor; Erbium; fluoridy; phthalocyanine; ženské pohlaví; screeningové testy protinádorových léčiv; Nanospheres; Mice, Nude; Yttrium; Molecular Structure; Structure-Activity Relationship; lidé; Photochemotherapy; Antineoplastic Agents; Mice; protinádorové látky; nanokuličky; Photosensitizing Agents; Isoindoles; Ytterbium; experimentální nádory; myši; fotosenzibilizující látky; molekulární struktura; Dose-Response Relationship, Drug; photodynamic therapy; Cell Proliferation; oxid křemičitý; energy transfer; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; upconversion nanospheres; isoindoly; zvířata; erbium; fotochemoterapie; yterbium; singlet oxygen; myši nahé; Neoplasms, Experimental; nádorové buněčné linie; ytrium; Humans